Analysis of the horizontal two‐dimensional near‐surface structure of a winter tornadic vortex using high‐resolution in situ wind and pressure measurements. Issue 12 (29th June 2015) - Kato, Ryohei; Kusunoki, Kenichi; Sato, Eiichi; Mashiko, Wataru; Inoue, Hanako Y.; Fujiwara, Chusei; Arai, Ken‐ichiro; Nishihashi, Masahide; Saito, Sadao; Hayashi, Syugo; Suzuki, Hiroto
Abstract The horizontal two‐dimensional near‐surface structure of a tornadic vortex within a winter storm was analyzed. The tornadic vortex was observed on 10 December 2012 by the high‐resolution in situ observational linear array of wind and pressure sensors (LAWPS) system in conjunction with a high‐resolution Doppler radar. The 0.1 s maximum wind speed and pressure deficit near the ground were recorded as 35.3 m s−1 and −3.8 hPa, respectively. The horizontal two‐dimensional distributions of the tornadic vortex wind and pressure were retrieved by the LAWPS data, which provided unprecedented observational detail on the following important features of the near‐surface structure of the tornadic vortex. Asymmetric convergent inflow toward the vortex center existed. Total wind speed was strong to the right and rear side of the translational direction of the vortex and weak in the forward part of the vortex possibly because of the strong convergent inflow in that region. The tangential wind speed profile of the vortex was better approximated using a modified Rankine vortex rather than the Rankine vortex both at 5 m above ground level (agl) and 100 m agl, and other vortex models (Burgers‐Rott vortex and Wood‐White vortex) were also compared. The cyclostrophic wind balance was violated in the core radius R0 and outside the core radius in the forward sector; however, it was held with a relatively high accuracy of approximately 14% outside the core of the vortex in the rearward sector (from 2 R0 to 5 R0) near the ground.